2011
DOI: 10.1038/mt.2011.89
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Adenovirus-Mediated hNIS Gene Transfer and 131I Radioiodine Therapy as a Definitive Treatment for Localized Prostate Cancer

Abstract: We have developed a replication-competent adenovirus (Ad5-yCD/mutTK(SR39)rep-hNIS) armed with two suicide genes and the human sodium iodide symporter (hNIS) gene. In this context, hNIS can be used as a reporter gene in conjunction with nuclear imaging and as a potentially therapeutic gene when combined with (131)I radioiodine therapy. Here, we quantified the volume and magnitude of hNIS gene expression in the human prostate following injection of a high Ad5-yCD/mutTK(SR39)rep-hNIS dose using a standardized inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 18 publications
(37 reference statements)
3
37
0
1
Order By: Relevance
“…The data presented here corroborate this issue. But our findings also address a recent report from a clinical trials of a NIS expressing adenovirus that produced poor results with respect to uptake of radioiodine 26 . Barton et al observed that the mean absorbed dose from administration of their vector into recurrent prostate cancers was well below the dose needed for a favorable therapeutic outcome.…”
Section: Discussionsupporting
confidence: 85%
“…The data presented here corroborate this issue. But our findings also address a recent report from a clinical trials of a NIS expressing adenovirus that produced poor results with respect to uptake of radioiodine 26 . Barton et al observed that the mean absorbed dose from administration of their vector into recurrent prostate cancers was well below the dose needed for a favorable therapeutic outcome.…”
Section: Discussionsupporting
confidence: 85%
“…3, 45, 46 Previously, an oncolytic adenovirus-expressing NIS was shown by 99m TcO 4 -based SPECT/CT imaging to concentrate iodide in the virus-injected tumors of patients with prostate cancer. 4 Although the adenovirus used in this published clinical trial did not mediate tumor regressions, 47 the study did serve to establish the feasibility of exploiting NIS as a reporter gene for human oncolytic applications. We are hopeful that HSV will be able to replicate and spread faster than an oncolytic adenovirus in human prostate cancer.…”
Section: Discussionmentioning
confidence: 97%
“…hNIS has been demonstrated to be a potentially therapeutic gene for human PC 23. Six men had clinically localised PCa and received an intraprostatic injection of Ad5-yCD/mutTK (SR39) rep -hNIS under transrectal ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%